ANALISIS JANUARY EFFECT PADA RETURN SAHAM BERKAPITALISASI BESAR DAN KECIL DI BURSA EFEK JAKARTA PADA TAHUN 2004-2007 - Christian Putra (Business Management Journal, 2017)
In the beginning of the year, stock’s return has an abnormal return. Small capital stocks produce better return than the large capital stocks which listed in Bursa Efek Jakarta (BEJ). This anomaly is known as January Effect. That’s why, when turn over especially occurs in the beginning of trading market activity, many investor will invest their assets in small capital stocks. This research tries to found out whether there is or there isn’t January effect anomaly in Bursa Efek Jakarta in 2004 till 2007. This research uses non probability method which choses 30 stocks in each category. The significance level of the research is always bigger than 0.05 and the result shows us that there is no January effect in Bursa Efek Jakarta (BEJ) from 2004 till 2007. Key Words- Return, January Effect. Stocks